ANTI-INFLAMMATORY ACTIVITY OF METHANOLIC EXTRACT OFAMORPHOPHALLUS PAEONIIFOLIUS AND ITS POSSIBLE MECHANISM - SHANKHAJIT DE,; YADU NANDAN DEY,; AJOY KUMAR GHOSH, (International Journal of Pharma and Bio Sciences, 2010)
Inflammation is a tissue reaction to infection, irritation or foreign substances. The tubers of Amorphophallus paeoniifolius are anti-inflammatory in nature and traditionally used in inflammations. The tubers were dried under shade and made to fine powder and extracted successively with petroleum ether, chloroform, methanol and water by using soxhlet extractor. For the assessment of the anti-inflammatory activity of the extracts at the dose of 200 and 400 mg/ kg, we used carrageenan induced paw edema model in rats. The standard drug diclofenac sodium at the dose of 5 and 10 mg/ kg were administered. For the assessment of antihistaminic effect, we measured triple responses in guinea pigs and used isolated guinea pig ileum preparation for bio assay. Results show that only the methanol extracts have got prominent anti-inflammatory activity. The results of the bio assay and triple response results also show that the methanol extract has got anti-histaminic activity.